2010
DOI: 10.1007/s11595-010-0152-6
|View full text |Cite
|
Sign up to set email alerts
|

Compound rejuvenation of polymer modified asphalt binder

Abstract: The objective of this research was to show a way to conduct rejuvenation of aged polymer modified asphalt binder (PMB) successfully. To fully evaluate and understand the rejuvenation of aged PMB, the Penetration grade tests including penetration, soften point, ductility and elastic recovery and Superpave TM PG grade tests including DSR, BBR and DDT were conducted. The rejuvenation effect of aged PMB by utilizing a fluid recycling agent in common use for binder rejuvenation was evaluated. And then the compound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The reduction rate for both low and high PG temperature is almost linear as indicated by high R 2 values in the Fig. 2 (the regression equations are also [24,9] Lei et al [11], and Ma et al [25] who have all demonstrated almost linear decrease in high and low temperature parameters with increasing rejuvenator dose. Fig.…”
Section: Resultsmentioning
confidence: 65%
“…The reduction rate for both low and high PG temperature is almost linear as indicated by high R 2 values in the Fig. 2 (the regression equations are also [24,9] Lei et al [11], and Ma et al [25] who have all demonstrated almost linear decrease in high and low temperature parameters with increasing rejuvenator dose. Fig.…”
Section: Resultsmentioning
confidence: 65%
“…It complies with the principle of sustainable development to recycle PMB after its service life ends. Researchers tried to investigate the recyclability of PMB, especially the most widely-used SBS modified bitumen [203][204][205][206][207][208][209]. Although some of these investigations concluded that it is technically feasible to recycle aged PMB by adding rejuvenators or virgin bitumen [203][204][205][206], there is still no widelyaccepted PMB recycling technique available today, which also affects the popularization of PMB in turn.…”
Section: Future Developmentsmentioning
confidence: 99%
“…In terms of partial mixing in the mixing process of recycled asphalt mixture and high-percentage recycled hot-mixture asphalt, Shirodkar et al plotted a mixing curve at different degrees of mixing and observed the influence of partial mixing on the selection of new asphalt grade [12,13]. e utilization of recycling agent is an effective means to improve the content of RAP [14,15]. e recycling agent is a type of low-viscosity oil, which is characterized by low viscosity, low solubility, and high aromatic content.…”
Section: Introductionmentioning
confidence: 99%